Functional determinants of dietary intake in community-dwelling older adults: a DEDIPAC (DEterminants of DIet and Physical ACtivity) systematic literature review. Issue 10 (12th February 2018) - Kiesswetter, Eva; Poggiogalle, Eleonora; Migliaccio, Siliva; Donini, Lorenzo Maria; Sulmont-Rossé, Claire; Feart, Catherine; Suwalska, Aleksandra; Wieczorowska-Tobis, Katarzyna; Pałys, Wiktor; Łojko, Dorota; Saba, Anna; Sinesio, Fiorella; et al.
Abstract: Objective: The identification of determinants of dietary intake is an important prerequisite for the development of interventions to improve diet. The present systematic literature review aimed to compile the current knowledge on individual functional determinants of dietary intake in community-dwelling older adults. Design: A systematic search was performed in PubMed, Scopus, Web of Science and the Cochrane Library. Titles, abstracts and full texts were screened according to predefined inclusion and exclusion criteria. Studies were included when focusing on dietary intake as an outcome and on chemosensory, oral, cognitive or physical function as a determinant. Setting: Community. Subjects: Older adults at least 65 years old without acute or specific chronic diseases. Results: From initially 14 585 potentially relevant papers, thirty-six were included. For chemosensory, cognitive and physical function only a few papers were found, which reported inconsistent results regarding the relationship to dietary intake. In contrast, oral function was extensively studied ( n 31). Different surrogates of oral function like dental status, number of teeth, bite force or chewing problems were associated with food as well as nutrient intakes including fibre. As all except six studies had a cross-sectional design, no causal relationships could be derived. Conclusions: Among functional determinants of dietary intake oral factors are well documented in older adults, whereas the role of other functional determinants remains unclear and needs further systematic research.